Development and validation of a modularized external fixator for generating standardized fracture healing micromotions in rats - Weichen Qi (The British Editorial Society of Bone & Joint Surgery, 2021)
Aims: To fully verify the reliability and reproducibility of an experimental method in generating standardized micromotion for the rat femur fracture model. Methods: A modularized experimental device has been developed that allows rat models to be used instead of large animal models, with the aim of reducing systematic errors and time and money constraints on grouping. The bench test was used to determine the difference between the measured and set values of the micromotion produced by this device under different simulated loading weights. The displacement of the fixator under different loading conditions was measured by compression tests, which was used to simulate the unexpected micromotion caused by the rat’s ambulation. In vivo preliminary experiments with a small sample size were used to test the feasibility and effectiveness of the whole experimental scheme and surgical scheme. Results: The bench test showed that a weight loading < 500 g did not affect the operation of experimental device. The compression test demonstrated that the stiffness of the device was sufficient to keep the uncontrollable motion between fracture ends, resulting from the rat’s daily activities, within 1% strain. In vivo results on 15 rats prove that the device works reliably, without overburdening the experimental animals, and provides standardized micromotion reproductively at the fracture site according to the set parameters. Conclusion: Our device was able to investigate the effect of micromotion parameters on fracture healing by generating standardized micromotion to small animal models. Cite this article: Bone Joint Res 2021;10(11):714–722.